Applicability of a chitosan-perlite nanocomposite for removing Mn (II) by adsorption approach - dos Santos, Elisama V. [UNESP]; de Araújo, Eliane G.; Cabral, Sheila P. M.; Monteiro, Mayra K. Sales; Santos, José E. L.; Martínez-Huitle, Carlos A. [UNESP]; Fernandes, Nedja S. (Springer Nature, 2025)
This work aims to investigate the use of a chitosan-perlite nanocomposite as an adsorbent for removing Mn(II) from water. The nanocomposite was characterized by thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Scanning electron microscope (SEM) and Brunauer–Emmett–Teller (BET) analysis. The adsorbent was studied in aqueous solutions containing Mn(II), revealing that its maximum capacity was about 23.09 mg g−1 in 90 min at a concentration of 50 mg L−1 at 25 °C according the correlations obtained by Langmuir model. The concentration of Mn(II) was monitored by Square-Wave Cathodic Stripping Voltammetry (SWCSV) approach, which was previously standardized, using glassy carbon, Ag/AgCl (3 mol L−1—KCl) and platinum as working, reference and counter electrodes, respectively. The analysis of residuals from the linear regression proved that a linear response exists from 7.76 × 10–7 mol L−1 to 1.42 × 10–4 mol L−1, with regression coefficients greater than 0.9969, achieving a good linear relationship between Mn(II) concentration and current response at the analytic curve. Then, Mn(II) removal was monitored using the SWCSV approach determining that, under the best conditions, chitosan-perlite nanocomposite removed > 90% in 120 min, at adsorption tests. Consequently, this material seems to be a potential tool for environmental applications.
Keywords: Chitosan; Electroanalysis; Manganese; Nanocomposite; Perlite